Persistent Hyperactivity of Hippocampal Dentate Interneurons After a Silent Period in the Rat Pilocarpine Model of Epilepsy - Wang, Xiaochen; Song, Xinyu; Wu, Lin; Nadler, J. Victor; Zhan, Ren-Zhi (Frontiers in Cellular Neuroscience, 2016)
Profile of GABAergic interneuron activity after pilocarpine-induced status epilepticus (SE) was examined in the rat hippocampal dentate gyrus by analyzing immediate early gene expression and recording spontaneous firing at near resting membrane potential. SE for exact 2 hours or more than 2 hours was induced in the male Sprague-Dawley rats by an intraperitoneal injection of pilocarpine. Expression of immediate early genes was examined at 1 hour, 1 week, 2 weeks or more than 10 weeks after SE. For animals to be examined at 1 hour after SE, SE lasted for exact 2 hours was terminated by an intraperitoneal injection of diazepam. Spontaneous firing at near the resting membrane potential was recorded in interneurons located along the border between the granule cell layer and the hilus more than 10 weeks after SE. Results showed that both c-fos and activity-regulated cytoskeleton associated protein (Arc) in hilar GABAergic interneurons were up-regulated after SE in a biphasic manner; they were increased at 1 hour and more than 2 weeks, but not at 1 week after SE. Ten weeks after SE, nearly 60% of hilar GABAergic cells expressed c-fos. With the exception of calretinin (CR)-positive cells, percentages of hilar neuronal nitric oxide synthase (nNOS)-, neuropeptide Y (NPY)-, parvalbumin (PV)-, and somatostatin (SOM)-positive cells with c-fos expression are significantly higher than those of controls more than 10 weeks after SE. Without the resting membrane potential to be more depolarizing and changed threshold potential level in SE-induced rats, cell-attached recording revealed that nearly 90% of hilar interneurons fired spontaneously at near the resting membrane potential while only 22% of the same cell population did so in the controls. In conclusion, pilocarpine-induced SE eventually leads to a state in which surviving dentate GABAergic interneurons become hyperactive with a subtype-dependent manner; this implies that a fragile balance between excitation and inhibition exists in the dentate gyrus and in addition, the activity-dependent up-regulation of IEGs may underlie plastic changes seen in some types of GABAergic cells in the pilocarpine model of epilepsy.